Edukasi Deteksi Dini sebagai Upaya Preventif Kanker Payudara dan Edukasi Langkah Pengobatan Kanker Payudara - Fithriani Armin; Fatiya Juwita Hanum; Ida Rahmah Burhan; Hayatun Nufus; Nurul Hidayati (Warta Pengabdian Andalas, 2019)
October is celebrated as the month of caring breast cancer worldwide, pioneered by Susan G. Komen for the Cure, a foundation for breast cancer in the United States. The month of October was used as a momentum to increase awareness of the importance of recognizing breast cancer which is the key to reducing new cases and the stages of advanced breast cancer. The government is optimizing efforts to prevent and control breast cancer. The role of breast cancer survivors' organization, Lovepink Indonesia research partner, which consists of breast cancer survivors and warriors is needed in sharing knowledge and experience in breast cancer treatment. Based on this, the collaboration between partners and universities can be elaborated by conducting education, socializing the importance of early detection of breast cancer as well as educating treatment steps through medical treatment to the public delivered by patients who have survived with breast cancer. Counseling, sharing experiences and practices of SADARI and SADANIS explanations are the methods used. The results of the implementation of this activity were reviewed directly from the high enthusiasm of the participants as evidenced by the desire to follow the SADARI technique movement and the emergence of questions to survivors about the experience and safety of treatments such as chemotherapy. The importance of the results of community service will trigger public knowledge about breast cancer has an impact on reducing the stage of advanced breast cancer patients thereby improving the quality of life of people and sufferers.